Mapping QTLs for adult-plant resistance to powdery mildew and stripe rust using a recombinant inbred line population derived from cross Qingxinmai × 041133 - Li, Yahui; Hu, Jinghuang; Lin, Huailong; Qiu, Dan; Qu, Yunfeng; Du, Jiuyuan; Hou, Lu; Ma, Lin; Wu, Qiuhong; Liu, Zhiyong; Zhou, Yijun; Li, Hongjie (Frontiers in Plant Science, 2024)
A recombinant inbred line (RIL) population derived from wheat landrace Qingxinmai and breeding line 041133 exhibited segregation in resistance to powdery mildew and stripe rust in five and three field tests, respectively. A 16K Genotyping By Target Sequencing (GBTS) SNP array-based genetic linkage map was used to dissect the QTL for the disease resistance. Four and seven QTL were identified for the adult-plant resistance (APR) against powdery mildew and stripe rust. QPm.caas-1B and QPm.caas-5A on chromosomes 1B and 5A were responsible for the APR against powdery mildew in line 041133. QYr.caas-1B, QYr.caas-3B, QYr.caas-4B, QYr.caas-6B.1, QYr.caas-6B.2, and QYr.caas-7B detected on the five B-genome chromosomes of line 041133 conferred its APR to stripe rust. QPm.caas-1B and QYr.caas.1B were co-localized with the pleiotropic locus Lr46/Yr29/Sr58/Pm39/Ltn2. A Kompetitive Allele Specific Polymorphic (KASP) marker KASP_1B_668028290 was developed to trace QPm/Yr.caas.1B. Four lines pyramiding six major disease resistance loci PmQ, Yr041133, QPm/Yr.caas-1B, QPm.caas-2B.1, QYr.caas-3B, and QPm.caas-6B were developed. They displayed effective resistance against both powdery mildew and stripe rust at the seedling and adultplant stages.